The woman inside : a novel - Scott, E. G. (Dutton, 2019)
Rebecca didn<U+2019>t know love was possible until she met Paul, a successful, charismatic, married man with a past as dark as her own. Their pain drew them together with an irresistible magnetism; they sensed that they were each other<U+2019>s ideal (and perhaps only) match. But twenty years later, Paul and Rebecca are drowning as the damage and secrets that ignited their love begin to consume their marriage. Paul is cheating on Rebecca, and his affair gets messy fast. His mistress is stalking them with growing audacity when Rebecca discovers Paul<U+2019>s elaborate plan to build a new life without her. And though Rebecca is spiraling into an opiate addiction, it doesn<U+2019>t stop her from coming up with a devious plot of her own, and this one could end absolutely everything. What follows is an unpredictable and stylish game of cat and mouse<U+2014>a shocking tale of unfaithfulness and unreliability that will keep you racing until the final twist and make you wonder how well you really know your spouse.